Evaluación de métodos de conservación como inhibidores de microorganismos patógenos en extracto de café (Coffea arabica l.) - Conforme Ozaeta, Gema Gabriela (2016)
This study aimed to evaluate conservation methods as inhibitors of pathogenic microorganisms in coffee extract (Coffea arabica L) for which experimental research facilities established of fruits and vegetables Agricultural Polytechnic school of Manabi, site Lemon, parish Calceta, Bolivar canton. Four study treatments (independent variable), two chemical type (: T1: potassium sorbate, T2:Sodium Benzoate) were implemented; and two physical type (T3: Sterilization, T4: vacuum), determining different types of pathogens microorganisms (dependent variable), and aerobic plate counts, total coliforms, Escherichia coli and molds are. Three replicates were applied. For statistical analysis of the information, a binary or binomial logistic regression study was carried out, establishing the relationship between the variables. The results expressed at mesophilic safety for the samples treated with physical methods, while treatments with chemical method demonstrated significant to control this variable. For other microbiological safety attributes was obtained from all treatments. The Cost method conservation best treatment is estimated that through the results statistics were the two physical reported that conservation Sterilization is more economical than vacuum, the chemical methods are not within the costs involved due to contamination evidenced in microbiological analysis.